When Do Newborns Die? Timing and Cause-Specific Neonatal Death in Neonatal Intensive Care Unit at Referral Hospital in Gedeo Zone: A Prospective Cohort Study - Akine Eshete; Sileshi Abiy (Hindawi Limited, 2020)
Background. Maternal, newborn, and child health have a high stake in the global health agenda, however, neonates' risk of dying is unacceptable in the world. Ethiopia is one of the countries with high burden of neonatal morbidity and mortality. Yet, timing and cause-specific neonatal death are under-investigated. The present study aimed to determine the timing and cause-specific neonatal death. Methods. We conducted a prospective cohort study at Dilla University Referral Hospital Neonatal Care Unit from November 2016 to January 2018. All admitted neonates to the neonatal care unit were followed from cohort entry up to the occurrence of an event (death) or end of follow-up. We generated descriptive statistics to determine the timing of neonatal death and the cause of deaths. Results. Overall, 11.6% of neonates died during the follow-up. We found that 34.0% and 64.3% of deaths occurred during the first and second weeks of neonatal life, respectively. Neonatal sepsis and low birth weight were the main causes of death and hospital admission. Jaundices and low birth weight were the most common causes of death during the early neonatal period, whereas birth asphyxia, low birth weight, and sepsis were during late neonatal life. However, for other causes of death, the slight difference was seen between the death patterns in early and late neonatal periods. Conclusions. The timing and cause-specific neonatal deaths were varying among different time of the neonatal periods that needs to design context-based policy and interventions.